Spatial Learning of Mice Lacking a Neuron-Specific Epidermal Growth Factor Family Protein, NELL2 - Shogo Matsuyama; Nobutaka Doe; Naoki Kurihara; Katsuyuki Tanizawa; Shun'ichi Kuroda; Hiroyuki Iso; Masato Horie (Elsevier, 2005)
NELL2 is a neuron-specific thrombospondin-1-like extracellular protein containing six epidermal growth factor-like domains. We previously disrupted the NELL2 gene in mice by gene targeting and showed that long-term potentiation is enhanced in vivo in the dentate gyrus of NELL2-deficient mice. To further elucidate the physiological roles of NELL2, we performed a behavioral characterization of NELL2−/− and their heterozygous control mice. NELL2-deficient mice exhibited learning impairment in the Morris water maze task. However, we observed no difference in passive avoidance learning between NELL2−/− and NELL2+/− mice. These observations suggest that NELL2 plays an important role in hippocampus-dependent spatial learning and that emotional learning does not depend critically on NELL2. Keywords:: NELL2, epidermal growth factor, thrombospondin, hippocampus, spatial learning